THE IMPACT OF IMPROVED RURAL WATER SUPPLIES ON THE HAMAR AKD HUNR TRIBES OF SOUTH-WESTERN KORDOFAN - A GEOGRAPHICAL ANALYSIS (1971)
This thesis attempts geographical analysis of the impact of Sudan's deep bore programmes on water-deficient and under-developed South-Western Kordofan; it is based partly on existing published materials and partly but more importantly on extensive field investigation. The main finding is that deep bore programmes have helped to transform South-Western Kordofan socially and economically. Chapter one of the thesis outlines the various mechanisms through which this transformation has been achieved. In the analysis, use is made of Knetsch's approach of comparing conditions in two culturally and physically similar areas, one of which has been provided with a change-inducing factor, and of attributing any observed differences between the two areas to its Operation. Chapter two contains a short account of the resources of South-Western Kordofan, both physical and human. Particular attention is paid to solid geology, on which the occurrence of subsurface water depends, to the natura of the superficial deposits, and to rainfall and Vegetation. Conflicting principles of need and balanced exploitation of resources have characterized the allocation of boreholes in space and time. Chapter three examines the implications of such conflicting principles for the distribution pattern of deep bores in South-Western Kordofan. In this chapter the concept is introduced of 'usable land', which is a function of the availability of water; an attempt is also made to determine hypothetically what should be the appropriate maximum distance between one borehole and another that would make for the Optimum exploitation of agricultural land and grazing of South-Western Kordofan. The Impact of the deep bore programmes on South-Western Kordofan's major economic activities is dealt with in three chapters. Chapter four explains why pastoralists may continue to be migratory even when adequate perennial water supplies are available; it also suggests how the deep bore programmes may create more grazing problems unless accompanied by well organized pasture management. Chapter five shows that the cropped area has increased considerably since the borehole: programmes began, but because attitudes towards cultivation vary widely, it is not possible to determine the precise contribution made by the deep bare programes to the expansion in the area under cultivation. The increase in cropped area has led to a reduction in the area under ’gum-gardens', but this has not been accompanied by a decline in gum production. Chapter six explains why and asks whether the Arabs will continue to invest their efforts in gum tapping if other and more rewarding sources of employment are open to them. The distribution of Services is strongly influenced by the availability of water. Since the population size of a settlement is limited by the amount of water it can provide in the dry season, the question is posed in chapter seven whether every deep bore settlement will possess population large enough for the Optimum use of all essential Services. The thesis ends with a short chapter which review a the role which the deep bore programes can and should play in the future development of South-Western Kordofan.